Method for recycling negative electrode material of waste lithium ion battery and lithium ion secondary battery

By using a method of roasting, water immersion treatment, and reaction of waste lithium-ion battery anode materials with ammonium bifluoride and a reducing agent, the problems of high energy consumption and difficulty in removing impurities in traditional recycling methods are solved, achieving efficient and low-energy recycling of anode materials and improving material purity and recycling efficiency.

CN120280590BActive Publication Date: 2025-11-18NANCHANG HANGKONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510409133.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-11-18
Estimated Expiration
2045-04-02

AI Technical Summary

Technical Problem

Existing technologies are insufficient for the efficient recycling of waste lithium-ion battery anode materials, especially graphite materials. Furthermore, traditional methods are energy-intensive and difficult to remove impurities, resulting in low recycling efficiency and low purity.

Method used

The method involves mixing and roasting waste negative electrode material with ammonium bifluoride, leaching it in water, reacting it with a reducing agent, separating impurities through alkaline precipitation, and concentrating the leachate to recover ammonium bifluoride. This approach achieves efficient recovery and high-value-added utilization of all materials.

Benefits of technology

It achieves green closed-loop recycling of waste lithium-ion battery anode materials, reduces energy consumption, improves the purity and added value of recycled anode materials, simplifies the recycling process, and reduces the introduction of impurities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120280590B_ABST
    Figure CN120280590B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of battery recycling, and particularly discloses a recycling method of waste lithium ion battery negative electrode material and a lithium ion secondary battery. The recycling method comprises the following steps: discharging and disassembling and separating the waste lithium ion battery to obtain a waste shell, waste positive electrode material, waste negative electrode material and waste diaphragm material; crushing and screening the waste negative electrode material to obtain waste negative electrode powder; mixing the waste negative electrode powder with ammonium hydrogen fluoride, and baking the mixture in an inert gas atmosphere at 100-500 DEG C for a preset time; performing water immersion treatment on the baking product, and performing solid-liquid separation on the obtained slurry to obtain a first leaching solution and regenerated negative electrode material; mixing and reacting the first leaching solution with a reducing agent, and performing solid-liquid separation to obtain a second leaching solution and copper residue; mixing and reacting the second leaching solution with alkali, and performing solid-liquid separation to obtain a third leaching solution and positive electrode precursor residue; and concentrating the third leaching solution to obtain recycled ammonium hydrogen fluoride. According to the application, green closed-loop recycling of various materials can be realized, and the energy consumption is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery recycling technology, and in particular to a method for recycling waste lithium-ion battery negative electrode materials and a lithium-ion secondary battery. Background Technology

[0002] With the rapid development of energy storage, electronic products, electric vehicles, and medical equipment, a large number of waste lithium-ion batteries have been generated, making their recycling an urgent need. Currently, the mainstream recycling methods used by enterprises are as follows: After the lithium-ion batteries are discharged, they undergo multi-stage crushing and separation to separate the waste separator, waste electrode materials (including positive and negative electrode materials), and current collectors (including copper and aluminum foil), while also separating the electrolyte. The resulting waste electrode materials are then subjected to pyrometallurgical or hydrometallurgical treatment. Pyrometallurgical treatment involves high-temperature melting of the waste electrode materials to extract valuable metals (such as Ni, Co, Mn, and Li). During this process, the negative electrode material is decomposed, making efficient recycling difficult. Hydrometallurgical recycling can recover various valuable metals, but the recovery efficiency of materials such as graphite is low when processing negative electrode materials. Graphite may be damaged or dissolved during leaching. Therefore, currently, in industry, negative electrode materials are often incinerated before chemical leaching, making it difficult to achieve recycling of negative electrode materials.

[0003] Current research on anode material recycling often focuses on the residue after chemical leaching. However, the residue typically contains very little positive electrode metal, rendering it essentially worthless for recycling. Therefore, existing anode material recycling efforts primarily concentrate on structural repair and regeneration of the anode material (usually graphite), with relatively little discussion on impurity removal and reuse. Furthermore, traditional waste lithium-ion battery recycling processes often require multi-stage crushing and sorting to separate the waste electrode material from the current collector. The resulting material is often only a few tens of micrometers in size. This crushing process not only consumes enormous amounts of energy but also introduces other impurities, affecting recycling efficiency and material purity.

[0004] On the other hand, during their research on waste lithium-ion batteries, the inventors discovered that many waste lithium-ion batteries are currently overused, resulting in issues such as bulging and leakage in the battery packs. This exposes the battery cells to air, causing the negative electrode current collector—copper foil—to oxidize and pulverize, forming copper oxides. These copper oxides are often impossible to separate from the current collector using common crushing and screening processes, leading to a concentration of copper in the waste negative electrode material and increasing recycling difficulty. Furthermore, before dismantling existing waste lithium-ion batteries, they are often soaked in brine for discharge. The brine often damages the outer casing and plastic protective materials, allowing it to enter the battery cell. This also causes reactions in the negative electrode current collector, making subsequent separation of the negative electrode material from the copper current collector difficult. Therefore, some waste negative electrode materials contain high levels of copper and related compounds. Traditional recycling methods are ineffective in removing these impurities, or after removal, they become mixed with useful metals, making separation difficult. This hinders the high-value recycling of waste negative electrode materials. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a method for recycling waste lithium-ion battery anode materials, which can realize green closed-loop recycling of each part of the materials and has low energy consumption.

[0006] To address the aforementioned technical problems, this invention provides a method for recycling waste lithium-ion battery negative electrode materials, comprising the following steps:

[0007] (1) Discharge the waste lithium-ion battery to obtain the discharged battery;

[0008] (2) Disassemble and separate the discharged battery to obtain waste casing, waste positive electrode material, waste negative electrode material and waste separator material;

[0009] (3) The waste negative electrode material is crushed and screened to obtain waste negative electrode powder; the average particle size of the waste negative electrode powder is ≥150μm and its Cu content is ≥2wt%;

[0010] (4) Mix the waste negative electrode powder with ammonium bifluoride, and then calcine it at 100~500℃ in an inert gas atmosphere for a preset time to obtain the calcined product;

[0011] (5) The roasted product is subjected to water immersion treatment, and the resulting slurry is separated into solid and liquid components to obtain the first leachate and the regenerated negative electrode material;

[0012] (6) The first leachate is mixed with a reducing agent and reacted, and then the solid and liquid are separated to obtain a second leachate and copper slag; wherein the reducing agent is selected from one or more of manganese powder, cobalt powder, nickel powder and aluminum powder;

[0013] (7) The second leachate is mixed with alkali and reacted, and then the solid and liquid are separated to obtain the third leachate and the positive electrode precursor residue;

[0014] (8) The third leachate is concentrated to obtain recovered ammonium fluoride.

[0015] As an improvement to the above technical solution, step (6) includes:

[0016] (6.1) The first leachate is first mixed with ammonium bifluoride, then mixed with a solvent, and the crystallization is allowed to proceed for a predetermined time. Then, solid-liquid separation is performed to obtain the fourth leachate and aluminum-containing slag.

[0017] (6.2) The fourth leachate is mixed with a reducing agent and reacted, and then the solid and liquid are separated to obtain the second leachate and copper slag.

[0018] As an improvement to the above technical solution, in step (4), the weight ratio of the waste negative electrode powder to the ammonium bifluoride is (2~6):(4~8); the calcination temperature is 150~350℃, and the calcination time is 60~180min; the inert gas is selected from one or more of nitrogen, argon, and helium; and / or

[0019] In step (5), the leaching temperature is 30~70℃, the leaching time is 20~100min, and the liquid-to-solid ratio is (1~20):1; and / or

[0020] In step (6), the molar ratio of the reducing agent to copper ions in the first leachate is (1~5):1, the reaction time after mixing is 5~60 min, and the reaction temperature is 15~80℃; and / or

[0021] In step (7), the pH of the second leachate is adjusted to 6-11 using an alkali, wherein the alkali is selected from sodium hydroxide, potassium hydroxide, or ammonia; and / or

[0022] In step (8), the concentration temperature is 70~150℃ and the concentration time is 0.5~5h.

[0023] As an improvement to the above technical solution, in step (4), the weight ratio of the waste negative electrode powder to the ammonium bifluoride is (4~5.5):(4.5~6); the calcination temperature is 180~300℃, and the calcination time is 70~150min; the inert gas is argon; and / or

[0024] In step (5), the leaching temperature is 41~70℃, the leaching time is 42~100min, and the liquid-solid ratio is (2~15):1;

[0025] In step (6), the molar ratio of the reducing agent to copper ions in the first leaching solution is (3~5):1, the reaction time after mixing is 10~45 min, and the reaction temperature is 20~60℃; and / or

[0026] In step (7), the pH of the second leachate is adjusted to 6-8 using an alkali, wherein the alkali is ammonia; and / or

[0027] In step (8), the concentration temperature is 70~100℃ and the concentration time is 0.5~3h.

[0028] As an improvement to the above technical solution, in step (4), the weight ratio of the waste negative electrode powder to the ammonium bifluoride is 4:6; the calcination temperature is 250℃, and the calcination time is 150min; the inert gas is argon; and / or

[0029] In step (5), the leaching temperature is 60℃, the leaching time is 60 min, and the liquid-to-solid ratio is 10:1; and / or

[0030] In step (6), the molar ratio of the reducing agent to the copper ions in the first leaching solution is 3:1, the reaction time after mixing is 30 min, and the reaction temperature is 25℃; and / or

[0031] In step (7), the pH of the second leachate is adjusted to 7-8 using an alkali, wherein the alkali is ammonia.

[0032] As an improvement to the above technical solution, in step (6.1), the concentration of ammonium bifluoride in the mixture obtained by mixing the first leachate and ammonium bifluoride is 6~20wt%; and / or

[0033] The solvent is selected from methanol, ethanol, or isopropanol; the volume ratio of the solvent to the first leachate is (0.4~1.2):1; and / or

[0034] The temperature for dissolution and crystallization is 10~30℃, and the time for dissolution and crystallization is 20~100min.

[0035] As an improvement to the above technical solution, in step (6.1), the concentration of ammonium bifluoride in the mixture obtained by mixing the first leachate and ammonium bifluoride is 10~12wt%; and / or

[0036] The solvent is methanol; the volume ratio of the solvent to the first leachate is (0.8~1.1):1; and / or

[0037] The temperature for dissolution and crystallization is 20~30℃, and the time for dissolution and crystallization is 60~100min.

[0038] As an improvement to the above technical solution, in step (6.1), the solvent is added dropwise to the mixture obtained by mixing ammonium bifluoride and the first leachate, and the dropping rate is 2~10 mL / min.

[0039] As an improvement to the above technical solution, in step (1), the waste lithium-ion batteries are discharged using a sodium chloride solution; and / or

[0040] The waste lithium-ion batteries are one or more of the following: waste NCM batteries, waste NCA batteries, waste lithium manganese oxide batteries, and waste lithium cobalt oxide batteries; and / or

[0041] The average particle size of the waste negative electrode powder is 150~500μm, and its Cu content is 3~8wt%.

[0042] Accordingly, the present invention also discloses a lithium-ion secondary battery, which includes recycled negative electrode material obtained by the above-described recycling method for waste lithium-ion battery negative electrode material.

[0043] Implementing this invention for 10-45 minutes has the following beneficial effects:

[0044] In one embodiment of the present invention, a method for recycling waste lithium-ion battery anode materials involves a process of mixing and roasting the waste anode material with ammonium bifluoride, water leaching, reducing copper slag with a reducing agent, precipitating the cathode precursor slag with alkali, and concentrating the leachate to recover ammonium bifluoride. This process yields recycled anode material, copper slag, and cathode precursor slag, achieving separate recycling and high-value utilization of each component. Furthermore, ammonium bifluoride can be recycled, achieving a green closed-loop recycling process and reducing recycling costs. The recycling method in this embodiment does not damage the crystal structure of the anode material, introduces few impurities, and yields high-purity recycled anode material that can be directly used. Moreover, the recycling method in this embodiment eliminates the need for extensive grinding in the pre-processing stage, reducing energy consumption and minimizing the introduction of impurities. Attached Figure Description

[0045] Figure 1 This is a flowchart of a method for recycling waste lithium-ion battery negative electrode materials according to an embodiment of the present invention;

[0046] Figure 2 This is an electron microscope image of the regenerated negative electrode material obtained in Example 1 of the present invention;

[0047] Figure 3 This is another electron microscope image of the regenerated negative electrode material obtained in Example 1 of the present invention;

[0048] Figure 4 This is the XRD pattern of the regenerated negative electrode material obtained in Example 1 of the present invention;

[0049] Figure 5This is the XRD pattern of the regenerated negative electrode material obtained in Comparative Example 1 of this invention;

[0050] Figure 6 This is an electron microscope image of the regenerated negative electrode material obtained in Comparative Example 2 of this invention. Detailed Implementation

[0051] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be described in further detail below. It should be noted that, unless otherwise specified, all reagents used in the examples are commercially available.

[0052] See Figure 1 This invention discloses a method for recycling waste lithium-ion battery negative electrode materials, which includes the following steps:

[0053] S1: Discharge the used lithium-ion battery to obtain the discharged battery;

[0054] S2: Disassemble and separate the discharged battery to obtain waste casing, waste positive electrode material, waste negative electrode material and waste separator material;

[0055] S3: Crush and screen the waste negative electrode material to obtain waste negative electrode powder;

[0056] S4: Mix waste negative electrode powder with ammonium bifluoride, and then calcine it at 100~500℃ in an inert gas atmosphere for a preset time to obtain the calcined product;

[0057] S5: The roasted product is subjected to water immersion treatment, and the resulting slurry is separated into solid and liquid to obtain the first leachate and the regenerated negative electrode material.

[0058] S6: Mix the first leachate with the reducing agent, react, and then separate the solid and liquid to obtain the second leachate and copper slag;

[0059] S7: Mix the second leachate with alkali and react, then separate the solid and liquid to obtain the third leachate and the positive electrode precursor residue;

[0060] S8: Concentrate the third leachate to obtain recovered ammonium bifluoride.

[0061] The waste negative electrode powder has an average particle size ≥150μm and a Cu content ≥2wt%. It should be noted that the Cu content here refers to the Cu content calculated based on elemental copper, meaning that other copper compounds (such as CuO, Cu2O, etc.) that may be present in the waste negative ion powder are converted to elemental copper. The Cu content can be determined by ICP method. The particle size of the waste negative ion powder can be determined by laser particle size analyzer (such as Mastersizer 3000). The recycling method of this invention is applicable to waste negative electrode powder with larger particle sizes and higher copper content, eliminating the need for multi-stage crushing, reducing energy consumption, reducing impurities introduced by crushing, improving the purity of subsequent products, and increasing their added value.

[0062] The above embodiment, through a process of mixing and roasting waste anode material with ammonium bifluoride, water leaching, reducing copper slag with a reducing agent, precipitating positive electrode precursor slag with alkali, and concentrating the leachate to recover ammonium bifluoride, yields regenerated anode material, copper slag, and positive electrode precursor slag, achieving separate recovery and high-value utilization of each component. Furthermore, ammonium bifluoride can be recycled, achieving green closed-loop recycling and reducing recycling costs. The recycling method in this embodiment does not damage the crystal structure of the anode material, introduces few impurities, and yields high-purity regenerated anode material that can be directly used. In addition, the recycling method in this embodiment does not require extensive grinding in the pretreatment stage, reducing energy consumption and minimizing the introduction of impurities.

[0063] Specifically, in step S1, the spent lithium-ion batteries can be discharged using physical discharge or chemical discharge processes, but are not limited to these methods. Preferably, in some embodiments, a chemical discharge process is used, specifically, the spent lithium-ion batteries are immersed in an electrolyte solution for discharge. The electrolyte solution can be a manganese sulfate solution, a copper sulfate solution, or a sodium chloride solution, but is not limited to these. More preferably, discharge is performed using a sodium chloride solution (5~10wt%), with a discharge immersion time of 12~96 hours, after which the voltage drops below 1.5V.

[0064] Specifically, in step S2, the various parts are directly disassembled and separated to obtain waste outer shells (aluminum shells, steel shells, and other connecting wires and other hardware), waste positive electrode materials (waste positive electrode material plates and other accompanying impurities), waste negative electrode materials (waste negative electrode materials and other accompanying impurities), and waste separator materials, which are then recycled separately. This simplifies the subsequent recycling process and aligns with current technological development trends. Preferably, in some embodiments, low-temperature pyrolysis can be performed before disassembly to separate solvents (such as carbonate solvents) and electrolytes (such as LiPF2), preventing electrolyte volatilization during subsequent disassembly. Specifically, the low-temperature pyrolysis temperature is 150~250℃, and pyrolysis is carried out in an inert atmosphere. It should be noted that traditional disassembly processes generally involve multi-stage crushing directly after discharge, or multi-stage crushing and sorting after removing some peripheral connectors and shells of the battery cell. This process mixes various materials together. In this embodiment, each part is disassembled separately, facilitating subsequent recycling and simplifying the recycling process.

[0065] Specifically, in step S3, a common crusher in the art, such as a jaw crusher or a shear crusher, is used for crushing, but it is not limited to these. The recycling method in this embodiment has low requirements for crushing and does not require the use of high-energy-consuming crushing equipment such as ball mills. After crushing, some copper foil can be removed by simple sieving. It should be noted that the recycling method in this embodiment is applicable to waste negative electrode materials containing a large amount of copper, so it is not necessary to crush them to a very fine size to achieve the separation of copper foil and graphite. Specifically, in this embodiment, the average particle size of the waste negative electrode powder is ≥150μm, and the Cu content is ≥2wt%. Preferably, in some embodiments, the average particle size of the waste negative electrode powder is 150~500μm, and its Cu content is 3~8wt%. More preferably, the Cu content is 3~5wt%.

[0066] Preferably, in some embodiments, the waste negative electrode material is pyrolyzed before crushing to separate the binder (such as PVDF), and the thermal decomposition temperature is 450~600℃.

[0067] Specifically, in step S4, the inert gas is one or more of nitrogen, argon, and helium, but is not limited to these. The weight ratio of waste negative electrode powder to ammonium bifluoride is (2~6):(4~8), exemplarily 2:8, 2.5:7.5, 3:7, 3.5:6.5, 4:6, 5:5, or 6:4, but is not limited to these. The roasting time is 60~180 min, exemplarily 65 min, 80 min, 95 min, 110 min, 140 min, or 160 min, but is not limited to these. Through roasting, the metals and metal compounds in the waste negative electrode powder will form water-soluble compounds, which can then be removed by water leaching. Based on the above roasting conditions, the removal rate of each metal (and its compounds) in the waste negative electrode powder can reach more than 70%.

[0068] It should be noted that in some existing technologies, ammonium fluoride is used to calcine waste anode materials, followed by water leaching to remove impurities, resulting in recycled graphite. However, the Cu content in these waste anode materials is low, often below 0.2 wt%. When the inventors conducted experiments using waste anode materials with higher Cu content, they found that if ammonium fluoride is used for calcination, the removal rate of copper and its compounds is very low at lower temperatures (150~300℃), and they accumulate in the graphite. Therefore, multi-stage crushing and sorting are often required to separate Cu from the anode material. While using higher calcination temperatures (400~600℃) can improve the Cu removal rate, it damages the structure of the anode material, often requiring subsequent high-temperature repair. Therefore, this invention uses ammonium bifluoride for calcination, which can effectively improve the Cu removal rate and optimize the performance of the recycled graphite. Moreover, the calcination can be carried out at a lower temperature, which prevents damage to the structure of the negative electrode material. Furthermore, the inventors discovered that the structure of the regenerated negative electrode material (graphite) obtained through the above-mentioned calcination and water immersion process is more regular and orderly, which will further optimize its performance.

[0069] Preferably, in some embodiments, the weight ratio of waste negative electrode powder to ammonium bifluoride is (4~5.5):(4.5~6); the calcination temperature is 180~300℃, the calcination time is 70~150min, and the inert gas is argon. Based on the above calcination conditions, the removal rate of various metals (and their compounds) in the waste negative electrode powder after water immersion treatment can reach more than 80%.

[0070] More preferably, in some embodiments, the weight ratio of waste negative electrode powder to ammonium bifluoride is 4:6; the calcination temperature is 250°C and the calcination time is 150 min; the inert gas is argon. Based on the above calcination conditions, the removal rate of each metal (and its compounds) in the waste negative electrode powder after water immersion treatment can reach more than 92%.

[0071] Specifically, in step S5, the liquid-to-solid ratio is (1~25):1, exemplarily 1.5:1, 5:1, 8:1, 11:1, 14:1, 17:1, or 22:1, but not limited thereto. Preferably, it is (1~20):1. It should be noted that the liquid-to-solid ratio in this invention corresponds to mL / g or a proportionally scaled-down relationship, exemplarily such as L / kg, m 3 / t or μL / mg, but not limited to these.

[0072] Specifically, in step S5, the leaching temperature is 30~80℃, exemplarily 35℃, 42℃, 50℃, 60℃, 68℃ or 77℃, but not limited thereto, preferably 30~70℃. The leaching time is 20~120min, exemplarily 35min, 50min, 70min, 90min or 110min, but not limited thereto. Preferably 20~100min. Based on the above leaching conditions, the removal rate of various metals (and their compounds) in the waste negative electrode powder can reach more than 65%.

[0073] Preferably, in some embodiments, in step S5, the liquid-to-solid ratio is (2~15):1, the leaching temperature is 41~70℃, and the leaching time is 42~100min. Based on the above leaching conditions, the removal rate of various metals (and their compounds) in the waste negative electrode powder can reach more than 80%.

[0074] More preferably, in some embodiments, in step S5, the liquid-to-solid ratio is 10:1, the leaching temperature is 60°C, and the leaching time is 60 min. Based on the above leaching conditions, the removal rate of each metal (and its compounds) in the waste negative electrode powder can reach more than 90%.

[0075] Specifically, in step S6, the reducing agent is selected from one or more of manganese powder, cobalt powder, nickel powder, and aluminum powder. Specifically, the corresponding reducing agent can be added according to the type of waste lithium-ion battery to obtain a positive electrode precursor slag that can be directly used in the preparation process of positive electrode materials. Specifically, when the waste lithium-ion battery is a waste NCM battery, the reducing agent can be one or more of manganese powder, cobalt powder, and nickel powder; when the waste lithium-ion battery is a waste NCA battery, the reducing agent can be one or more of manganese powder, cobalt powder, and aluminum powder; when the waste lithium-ion battery is a waste lithium manganese oxide battery, the reducing agent can be manganese powder; when the waste lithium-ion battery is a waste lithium cobalt oxide battery, the reducing agent can be cobalt powder, but it is not limited to these. It should be noted that the above-mentioned reducing agents are all metals, i.e., manganese powder is manganese metal powder, and so on. By using the above-mentioned reducing agents for reduction, the copper complex in the first leaching solution can be reduced, preventing it from entering the positive electrode precursor slag and affecting the performance of the positive electrode material. Preferably, in some embodiments, manganese powder is selected as the reducing agent because it has high reaction efficiency.

[0076] Specifically, the molar ratio of the reducing agent to copper ions in the first leachate is (1~6):1, exemplarily 2:1, 3:1, 4:1, 5:1, or 5.5:1, but not limited thereto. Preferably, it is (1~5):1. The reaction time after mixing the first leachate and the reducing agent is 5~70 min, exemplarily 8 min, 15 min, 30 min, 40 min, 60 min, or 68 min, but not limited thereto. Preferably, it is 5~60 min. The reaction temperature after mixing the first leachate and the reducing agent is 15~80℃, exemplarily 20℃, 30℃, 40℃, 60℃, or 72℃, but not limited thereto. Based on these reduction reaction conditions, the removal rate of copper ions in the first leachate can reach more than 50%.

[0077] Preferably, in some embodiments, the molar ratio of the reducing agent to copper ions in the first leachate is (3~5):1, the reaction time after mixing is 10~45 min, and the reaction temperature is 20~60℃; based on these reduction reaction conditions, the removal rate of copper ions in the first leachate can reach more than 70%.

[0078] More preferably, in some embodiments, the molar ratio of the reducing agent to copper ions in the first leachate is 3:1, the reaction time after mixing is 30 min, and the reaction temperature is 25°C. Based on these reduction reaction conditions, the removal rate of copper ions in the first leachate can reach over 90%.

[0079] Specifically, in step S7, the pH of the second leachate is adjusted to 6-11 using an alkali, which causes Ni, Co, Mn, Al, etc., to precipitate as hydroxides, thereby obtaining a cathode precursor slag that can be used to prepare cathode materials. Exemplarily, the pH is adjusted to 7, 7.5, 8, 9, or 10, but is not limited to these. Through the above precipitation step, the content of each metal ion in the obtained third leachate is reduced to below 20 μg / L, and then high-purity ammonium bifluoride is recovered through a subsequent concentration process, achieving the recycling and reuse of ammonium bifluoride.

[0080] Specifically, in step S7, the alkali may be ammonia, sodium hydroxide, or potassium hydroxide, but is not limited to these. Ammonia is preferably used to prevent the introduction of other impurities.

[0081] Preferably, in some embodiments, in step S7, an alkali is used to adjust the pH of the second leachate to 6-8. The waste negative ion powder of the present invention is obtained by direct dismantling without acid leaching or other processes, and does not contain acid radical ions, thus allowing the precipitation of various metals to be completed at a relatively low pH. More preferably, in some embodiments, an alkali is used to adjust the pH of the second leachate to 7-8.

[0082] Specifically, in step S8, the third leachate can be concentrated by vacuum distillation or evaporation crystallization, but is not limited thereto. Preferably, in some embodiments, the third leachate is evaporated and crystallized at a temperature of 70~150°C for 0.5~5 hours, but is not limited thereto. Preferably, in some embodiments, the concentration temperature is 70~100°C and the concentration time is 0.5~3 hours.

[0083] Preferably, in some embodiments, when the waste lithium-ion battery is one or a mixture of waste NCM batteries, waste lithium manganese oxide batteries, or waste lithium cobalt oxide batteries, it is necessary to remove aluminum (and its compounds) from the waste negative electrode material. Specifically, by adding ammonium bifluoride to the leachate, a common ion effect will occur in the dissolution equilibrium system, causing aluminum ions to precipitate in the form of (NH4)3AlF6, thereby achieving aluminum removal. It should be noted that Al can be removed first, followed by Cu, or Cu can be removed first, followed by Al. More preferably, in some embodiments, step S6 includes:

[0084] S61: The first leachate is first mixed with ammonium bifluoride, then mixed with a solvent, and the crystallization is allowed to proceed for a preset time. Then, solid-liquid separation is performed to obtain the fourth leachate and aluminum-containing slag.

[0085] S62: Mix the fourth leachate with the reducing agent, react, and then separate the solid and liquid to obtain the second leachate and copper slag;

[0086] Through the above steps, Al can be separated from the first leachate, and then Cu can be separated. This leaves only metals similar to those in the lithium-ion battery cathode precursor in the second leachate.

[0087] Specifically, in step S61, the concentration of ammonium bifluoride in the mixture obtained by mixing the first leachate and ammonium bifluoride is 6-20 wt%, exemplarily 6.5 wt%, 10 wt%, 12 wt%, or 16 wt%, but not limited thereto. By controlling the above concentration, the concentration of Al ions in the mixture can be reduced to below 0.1 g / L, thus achieving full leaching. Preferably, the concentration of ammonium bifluoride in the mixture obtained by mixing the first leachate and ammonium bifluoride is 10-12 wt%. Based on this concentration, the concentration of Al ions in the mixture can be reduced to below 0.02 g / L.

[0088] Specifically, in step S61, the solvent is selected from methanol, ethanol, or isopropanol, but is not limited to these. By combining the solvent with ammonium bifluoride, the aluminum removal rate in the first leaching solution can be increased to over 80%, while if only one of them is used, the removal rate is only 50-60%. Preferably, methanol or ethanol is selected as the solvent because it has a higher removal rate; more preferably, methanol is selected because it has a lower cost.

[0089] Specifically, in step S61, the volume ratio of the solvent to the first leachate is (0.4~1.2):1, exemplarily 0.5:1, 0.6:1, 0.8:1, 0.9:1, or 1.1:1, but not limited thereto. Preferably, it is (0.8~1.1):1. The temperature for dissolution and crystallization is 10~30℃, exemplarily 12℃, 15℃, 18℃, 22℃, or 24℃, but not limited thereto. Preferably, it is 20~30℃. The duration of dissolution and crystallization is 20~100 min. Exemplarily 25 min, 40 min, 55 min, 70 min, or 88 min, but not limited thereto. Preferably, it is 60~100 min.

[0090] Preferably, in some embodiments, in step S61, the solvent is added dropwise to the mixture obtained by mixing ammonium bifluoride and the first leaching solution at a rate of 2-10 mL / min. This dropwise addition method can further improve the aluminum removal rate.

[0091] Preferably, in some embodiments, after dissolution and crystallization, the mixture is aged for 20 to 100 minutes, which can further improve the aluminum removal rate.

[0092] Accordingly, the present invention also discloses a lithium-ion secondary battery comprising the regenerated negative electrode material recovered by the above-described recycling method. Specifically, the regenerated negative electrode material obtained by the present invention has high purity and good structure, and can be directly used in batteries, but is not limited thereto.

[0093] Preferably, the lithium-ion secondary battery of the present invention further includes a positive electrode material prepared by a co-precipitation process from the positive electrode precursor slag obtained by the above-mentioned recycling method, copper foil prepared by electrolysis or rolling process from the copper slag recovered by the above-mentioned recycling method, and aluminum foil prepared by the aluminum slag recovered by the above-mentioned recycling method, but not limited thereto.

[0094] The present invention will be further described below with reference to specific embodiments:

[0095] Example 1

[0096] (1) Discharge the waste lithium-ion battery (NCM) to obtain the discharged battery;

[0097] (2) Disassemble and separate the discharged battery to obtain waste casing, waste positive electrode material, waste negative electrode material and waste separator material;

[0098] (3) The waste negative electrode material is crushed and sieved to obtain waste negative electrode powder; the average particle size of the waste negative electrode powder is 458 μm, and its chemical composition is shown in the table below. It should be noted that the following composition is calculated based on metal elements. In fact, each metal exists in the form of compounds, metals, etc.

[0099]

[0100] (4) The waste negative electrode powder and ammonium bifluoride were mixed at a weight ratio of 4:6, and then calcined at 250°C in an argon atmosphere for 150 min to obtain the calcined product.

[0101] (5) The calcined product was mixed with water at a ratio of 1:10 and leached at 60°C for 60 min. The resulting slurry was separated into solid and liquid components to obtain the first leachate and the regenerated negative electrode material. The removal rates were as follows: lithium 99.5%, manganese 99.12%, cobalt 98.47%, nickel 99.75%, copper 99.20%, and aluminum 99.33%. The removal rates were calculated as follows:

[0102]

[0103] In the formula, M1 is the mass (g) of the recycled negative electrode material, W1 is the mass fraction (wt%) of the metal in the recycled negative electrode material, M0 is the mass (g) of the waste negative electrode powder, and W0 is the mass fraction (wt%) of the metal in the waste negative electrode powder. The electron microscope image of the recycled negative electrode material obtained in this step is shown below. Figures 2-3 As shown in the figure, the scale structure of the regenerated anode material is clear and free of obvious impurities. The XRD pattern of the regenerated anode material obtained in this step is shown below. Figure 4 As shown in the figure, the regenerated negative electrode material has a complete crystal phase structure and sharp diffraction peaks, indicating good crystallinity. Furthermore, the absence of obvious impurity peaks indicates high purity.

[0104] (6) The first leachate was first mixed with ammonium bifluoride, and the concentration of ammonium bifluoride in the resulting mixture was 11.5 wt%. Then, methanol was added dropwise at a rate of 5 mL / min, and the mixture was dissolved and crystallized at 25 °C for 60 min, and then aged for 60 min. The solid and liquid were separated to obtain the fourth leachate and aluminum-containing slag. The aluminum removal rate was 88.46%. The aluminum removal rate was calculated according to the following formula:

[0105]

[0106] In the formula, ρ0 represents the Al content in the first leachate. 3+ The concentration of Al in the fourth leachate, ρ1 is the concentration of Al in the fourth leachate. 3+ The concentration is g / L; V0 is the volume of the first leachate, and V1 is the volume of the fourth leachate, mL.

[0107] (7) Manganese powder was added to the fourth leaching solution at a molar ratio of 3:1 between the reducing agent and copper ions in the fourth leaching solution. The mixture was reacted at 25°C for 30 min, and then the solid and liquid were separated to obtain the second leaching solution and copper slag. The removal rate of Cu was 98.99%. The removal rate of copper was calculated according to the following formula:

[0108]

[0109] In the formula, w 0 represents Cu in the fourth leachate 2+ concentration, w 1 represents Cu in the second leachate 2+ The concentration is g / L; V0 is the volume of the fourth leachate, and V1 is the volume of the second leachate, mL.

[0110] (8) The pH of the second leachate was adjusted to 8 using ammonia water, and then the third leachate and the positive electrode precursor residue were obtained by solid-liquid separation;

[0111] (9) The third leachate was evaporated and concentrated at 100°C for 2 hours to obtain recovered ammonium fluoride.

[0112] Comparative Example 1

[0113] This comparative example provides a method for recycling waste lithium-ion battery negative electrode materials, which includes the following steps:

[0114] (1) Discharge the waste lithium-ion battery (NCM) to obtain the discharged battery;

[0115] (2) Disassemble and separate the discharged battery to obtain waste casing, waste positive electrode material, waste negative electrode material and waste separator material;

[0116] (3) The waste negative electrode material is crushed and sieved to obtain waste negative electrode powder; the average particle size of the waste negative electrode powder is 458 μm, and its chemical composition is shown in the table below. It should be noted that the following composition is calculated based on metal elements. In fact, each metal exists in the form of compounds, metals, etc.

[0117]

[0118] (4) The waste negative electrode powder and ammonium fluoride were mixed at a weight ratio of 4:6, and then calcined at 250°C in an argon atmosphere for 150 min to obtain the calcined product.

[0119] (5) The roasted product was mixed with water at a ratio of 10:1 and leached at 60°C for 60 min. The resulting slurry was separated into solid and liquid components to obtain the first leaching solution and the regenerated negative electrode material. The removal rates of lithium, manganese, cobalt, nickel, copper, and aluminum were 99.62%, 99.75%, 99.62%, 99.44%, 55.87%, and 70.45%, respectively.

[0120] The XRD pattern of the regenerated anode material obtained in this comparative example is as follows: Figure 5 As shown in the figure, Cu is still present in the negative electrode material.

[0121] Comparative Example 2

[0122] This comparative example provides a method for recycling waste lithium-ion battery negative electrode materials, which includes the following steps:

[0123] (1) Discharge the waste lithium-ion battery (NCM) to obtain the discharged battery;

[0124] (2) Disassemble and separate the discharged battery to obtain waste casing, waste positive electrode material, waste negative electrode material and waste separator material;

[0125] (3) The waste negative electrode material is crushed and sieved to obtain waste negative electrode powder; the average particle size of the waste negative electrode powder is 458 μm, and its chemical composition is shown in the table below. It should be noted that the following composition is calculated based on metal elements. In fact, each metal exists in the form of compounds, metals, etc.

[0126]

[0127] (4) The waste negative electrode powder and ammonium fluoride were mixed at a weight ratio of 4:6, and then calcined at 500°C in an argon atmosphere for 150 min to obtain the calcined product.

[0128] (5) The roasted product was mixed with water at a ratio of 10:1 and leached at 60°C for 60 min. The resulting slurry was separated into solid and liquid components to obtain the first leaching solution and the regenerated negative electrode material. The removal rates of lithium, manganese, cobalt, nickel, copper, and aluminum were 99.79%, 99.95%, 99.94%, 99.95%, 74.53%, and 80.78%, respectively.

[0129] The electron microscope image of the regenerated negative electrode material obtained in this comparative example is shown below. Figure 6 As shown in the figure, the layered structure of the regenerated negative electrode material is unclear, and there are residual impurities on the surface.

[0130] The above description is a preferred embodiment of the invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principle of the invention, and these improvements and modifications are also considered to be within the scope of protection of the invention.

Claims

1. A method for recycling waste lithium-ion battery negative electrode materials, characterized in that, Includes the following steps: (1) Discharge the waste lithium-ion battery to obtain the discharged battery; (2) Disassemble and separate the discharged battery to obtain waste casing, waste positive electrode material, waste negative electrode material and waste separator material; (3) The waste negative electrode material is crushed and sieved to obtain waste negative electrode powder; the average particle size of the waste negative electrode powder is 150~500μm, and its Cu content is 3~8wt%; (4) The waste negative electrode powder is mixed with ammonium bifluoride and then calcined at 250°C in an inert gas atmosphere for a preset time to obtain the calcined product; wherein the weight ratio of the waste negative electrode powder to the ammonium bifluoride is 4:6; the calcination time is 150 min; and the inert gas is argon. (5) The roasted product is subjected to water immersion treatment, and the resulting slurry is separated into solid and liquid components to obtain the first leachate and the regenerated negative electrode material; (6) The first leachate is mixed with the reducing agent and reacted, and then the solid and liquid are separated to obtain the second leachate and copper slag; wherein the reducing agent is manganese powder, the molar ratio of the reducing agent to copper ions in the first leachate is (3~5):1, the reaction time after mixing is 10~45min, and the reaction temperature is 20~60℃. (7) The second leachate is mixed with alkali and reacted, and then the solid and liquid are separated to obtain the third leachate and the positive electrode precursor residue; (8) The third leachate is concentrated to obtain recovered ammonium fluoride.

2. The method for recycling waste lithium-ion battery negative electrode materials as described in claim 1, characterized in that, Step (6) includes: (6.1) The first leachate is first mixed with ammonium bifluoride, then mixed with a solvent, and the crystallization is allowed to proceed for a predetermined time. Then, solid-liquid separation is performed to obtain the fourth leachate and aluminum-containing slag. (6.2) The fourth leachate is mixed with a reducing agent and reacted, and then the solid and liquid are separated to obtain the second leachate and copper slag.

3. The method for recycling waste lithium-ion battery negative electrode materials as described in claim 1 or 2, characterized in that, In step (5), the leaching temperature is 30~70℃, the leaching time is 20~100min, and the liquid-to-solid ratio is (1~20):1; and / or In step (7), the pH of the second leachate is adjusted to 6-11 using an alkali, wherein the alkali is selected from sodium hydroxide, potassium hydroxide, or ammonia; and / or In step (8), the concentration temperature is 70~150℃ and the concentration time is 0.5~5h.

4. The method for recycling waste lithium-ion battery negative electrode materials as described in claim 1 or 2, characterized in that, In step (5), the leaching temperature is 41~70℃, the leaching time is 42~100min, and the liquid-solid ratio is (2~15):1; In step (7), the pH of the second leachate is adjusted to 6-8 using an alkali, wherein the alkali is ammonia; and / or In step (8), the concentration temperature is 70~100℃ and the concentration time is 0.5~3h.

5. The method for recycling waste lithium-ion battery negative electrode materials as described in claim 1 or 2, characterized in that, In step (5), the leaching temperature is 60℃, the leaching time is 60 min, and the liquid-to-solid ratio is 10:1; and / or In step (6), the molar ratio of the reducing agent to the copper ions in the first leaching solution is 3:1, the reaction time after mixing is 30 min, and the reaction temperature is 25℃; and / or In step (7), the pH of the second leachate is adjusted to 7-8 using an alkali, wherein the alkali is ammonia.

6. The method for recycling waste lithium-ion battery negative electrode materials as described in claim 2, characterized in that, In step (6.1), the concentration of ammonium bifluoride in the mixture obtained by mixing the first leachate with ammonium bifluoride is 6~20wt%; and / or The solvent is selected from methanol, ethanol, or isopropanol; the volume ratio of the solvent to the first leachate is (0.4~1.2):1; and / or The temperature for dissolution and crystallization is 10~30℃, and the time for dissolution and crystallization is 20~100min.

7. The method for recycling waste lithium-ion battery negative electrode materials as described in claim 2, characterized in that, In step (6.1), the concentration of ammonium bifluoride in the mixture obtained by mixing the first leachate and ammonium bifluoride is 10~12wt%; and / or The solvent is methanol; the volume ratio of the solvent to the first leachate is (0.8~1.1):1; and / or The temperature for dissolution and crystallization is 20~30℃, and the time for dissolution and crystallization is 60~100min.

8. The method for recycling waste lithium-ion battery negative electrode materials as described in claim 6 or 7, characterized in that, In step (6.1), the solvent is added dropwise to the mixture obtained by mixing ammonium bifluoride and the first leachate at a rate of 2 to 10 mL / min.

9. The method for recycling waste lithium-ion battery negative electrode materials as described in claim 1, characterized in that, In step (1), the waste lithium-ion batteries are discharged using a sodium chloride solution; and / or The waste lithium-ion batteries are one or more of the following: waste NCM batteries, waste NCA batteries, waste lithium manganese oxide batteries, and waste lithium cobalt oxide batteries.

10. A lithium-ion secondary battery, characterized in that, This includes recycled negative electrode materials obtained by the recycling method for waste lithium-ion battery negative electrode materials as described in any one of claims 1 to 9.